PENGGUNAAN MEDIA TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) UNTUK PEMBELAJARAN MAHASISWA UNIVERSITAS PGRI JOMBANG - Masruchan, Masruchan (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This article is the result of research on the use of the internet as a medium of learning in students of universitas pgri jombang. This study used descriptive qualitative approach. This research uses a descriptive qualitative approach. The data source for this research was obtained from primary data sources. The results of this research include 3 categories as follows: first, use of the internet as a medium of learning in universitas pgri jombang can be mapped into three categories, namely: the use of web searching facility, the use of e-mail facilities, and the use of e-learning (spada) facilities. Secondly, in terms of infrastructure, hardware to support internet-based learning is sufficient, but the amount of bandwidth is still very far from the standard requirements. Meanwhile, in terms of human resources, still need to increase their knowledge and skills in the field of tik for teachers and students to be able to implement an optimal internet-based learning. Third, universitas pgri jombang students responded very positively to the use of the internet as a medium of learning. Therefore, it is necessary to increase the quality and capacity of using information and communication technology media to optimize student learning both online and offline.